Risk Management Analysis and Bam Earthquake Crisis Using “Swot” Technique - Samad Fotouhi; maryam hoseinpoor; yasaman yari (مخاطرات محیط طبیعی, 2015)
Natural events and accidents cause lots of financial and life damages in the country yearly. It is important to pay more attention about this problem according to the country location and placement of cities on earthquake_ prone areas. One of the necessary measures is to use principles of crisis management in order to reduce risks, vigilance, confronting, reconstruction, rehabilitation. So crisis management is a dynamic process in the form of deliberate action, that is used before, during and after the crisis.The purpose of this research is to assessment and analysis of the bam earthquake hazard risk. This research has used swot technique analytic matrix in order to analysis information and present crisis management sterategies and bam earthquake risk.The results of the research show that disaster management has a lot of weaknesses. The results of this study can be used to manage the crisis in country of Iran in other earthquake. This research is an applied and normative _ analytical research.